Students' language achievement, attitude towards classroom relationship and cooperative learning strategies - Cerezo, Corazon Lomibao (2007)
The study investigated the effect of Cooperative Learning Strategies on the language achievement and attitude towards classroom relationship of the junior students from a public secondary high school in Dagupan City. The participants were two sections assigned as experimental and control group. The study used the qualitative-quantitative, mixed method design. The findings showed no significant differences in the language achievement between the 2 groups. This is attributed to the fact that the test administered evaluated more the cognitive skills which Cummins labeled Cognitive Academic Language Proficiency (CALP) rather than affective or social skills. It was shown that Cooperative Learning directly influences the attitude of the learner. When the teacher communicate positively inside the classroom, the students feel important, lift their self esteem and enhance social interaction in the class.